2002
DOI: 10.1152/ajpheart.00032.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic remodeling of heart during treatment of spontaneously hypertensive rats with enalapril

Abstract: We used spontaneously hypertensive rats to study remodeling of cardiac bioenergetics associated with changes in blood pressure. Blood pressure was manipulated with aggressive antihypertensive treatment combining low dietary salt and the angiotensin-converting enzyme inhibitor enalapril. Successive cycles of 2 wk on, 2 wk off treatment led to rapid, reversible changes in left ventricular (LV) mass (30% change in <10 days). Despite changes in LV mass, specific activities of bioenergetic (cytochrome-c oxidase, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…ANG II facilitates changes in mitochondrial cytochrome c content (99). These results demonstrate that ANG II can depress mitochondrial energy metabolism and that the augmentation of antioxidants due to upregulation of HO-1 may reverse this depression, resulting in amelioration of mitochondrial function (Fig.…”
Section: Role Of Ho In Blood Pressure Regulationmentioning
confidence: 61%
“…ANG II facilitates changes in mitochondrial cytochrome c content (99). These results demonstrate that ANG II can depress mitochondrial energy metabolism and that the augmentation of antioxidants due to upregulation of HO-1 may reverse this depression, resulting in amelioration of mitochondrial function (Fig.…”
Section: Role Of Ho In Blood Pressure Regulationmentioning
confidence: 61%
“…Since mitochondria, in association with myofibrils, represent a basic index of the potential cardiac work (Kayar et al, 1986;Barth et al, 1992), we suggest that, in the presence of both an accelerated contractile rhythm and a higher pumping capacity, the enlargement of the mitochondrial compartment provides the myofibrillar apparatus with an adequate amount of energetic compounds. A number of signalling mechanisms and transcription factors are known to contribute to the coordinated increase in mitochondrial content that is associated with cardiac growth in response to increased afterload (Leary et al, 2002, and references therein). The increase in the mitochondrial compartment of the compacta myocytes with growth, together with the smaller decrement of the myofibrillar compartment, suggests that the compacta may sustain a higher workload than the spongiosa.…”
Section: Discussionmentioning
confidence: 99%
“…Because AP-1 regulates cytochrome c expression (437), it was suggested that JNK may facilitate changes in the mitochondrial content of cytochrome c in response to ANG II (241).…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%